The Effect of Different Doses of Intraamniotic Digoxin on the Timing of Fetal Demise in Second Trimester Medical Abortions - Gulsah Aynaoglu Yildiz; Ragip Atakan Al (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: The World Health Organization recommends feticide for termination of pregnancy after 20 weeks of gestation, and the Royal College of Obstetricians & Gynecologists after 21 weeks and 6 days. Digoxin is a commonly used feticidal agent. This retrospective study aimed to show the effect of different doses of digoxin on the timing of fetal demise when used for feticide.